2019
DOI: 10.1007/s10708-019-10098-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in agricultural productivity: evidence from maize farm households in southern Ethiopia

Abstract: This study examines the impact of gender differences on maize productivity in Dawuro Zone, southern Ethiopia. Our study addressed the limitations of the previous studies in two ways. First, the study separately assessed gender differences in productivity between de facto female-headed households and de jure female-headed households and revealed that female-headed households are not homogenous. Second, the study separately examined the impacts of the covariates on male-headed households and female-headed househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 32 publications
12
68
1
2
Order By: Relevance
“…Male plot managers had the highest average quantity of seed used and the mean person hours of family labour used across all the three districts. This corroborates the observation by Gebre et al. (2019) that male plot managers have greater access to farm inputs compared to female plot managers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Male plot managers had the highest average quantity of seed used and the mean person hours of family labour used across all the three districts. This corroborates the observation by Gebre et al. (2019) that male plot managers have greater access to farm inputs compared to female plot managers.…”
Section: Resultssupporting
confidence: 91%
“…Male plot managers had the highest average quantity of seed used and the mean person hours of family labour used across all the three districts. This corroborates the observation by Gebre et al (2019) that male plot managers have greater access to farm inputs compared to female plot managers. There was no evidence of fertilizer use, except in Lira district where male plot managers recorded a minimal use of fertilizer perhaps due to contract farming with the brewery industry.…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Thus, Dawuro exhibits climatic variations from lowland to highland. The climatic variations have enriched Dawuro with a variety of tree species and natural vegetation/forests (Gebre et al 2019b). The majority of the Dawuro people (91%) live in rural areas (Negashi 2019), and their livelihood is based on a mixed crop-livestock production system.…”
Section: Backgrounds Of the Study Areamentioning
confidence: 99%
“…Third, women in Ethiopia play a significant role in maize production. For example, women in the Dawuro zone comprise, on average, 36% of the labour force in maize production (Gebre et al 2019b) and 29% in all crop sectors in Ethiopia (Palacios-Lopez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive information and discussion about access and control of household resources of this study area is found inGebre et al (2019b).…”
mentioning
confidence: 99%